Epistemological Crisis to Educational Reform: Reconstructing al-Faruqi’s Islamization of Knowledge for Islamic Education - Azlina Azlina; Abu Anwar (International Journal of Multidisciplinary Research of Higher Education, 2026)
Contemporary Islamic education is facing a profound epistemological crisis characterized by the dichotomy between religious and secular sciences, the dominance of positivistic and secular paradigms, and the weak integration of tawhidic values into knowledge development. This crisis has led to fragmented educational objectives and reduced curricular relevance to the needs of the Muslim community. The present study aims to critically examine the epistemological roots of this crisis and explore the applicability of Ismail Raji al-Faruqi’s concept of the Islamization of Knowledge as a reformative framework. Employing a library research method with descriptive-analytical techniques, the study focuses on al-Faruqi’s seminal work Islamization of Knowledge and relevant secondary literature. The findings reveal that the epistemological crisis stems primarily from the entrenched dichotomy of knowledge and the pervasive influence of secular paradigms. Al-Faruqi’s epistemological project, when reformulated through twelve practical steps, provides a comprehensive tawhidic epistemological model that can be operationalized in curriculum design, educational objectives, and pedagogical praxis. The implications of this reformulation highlight the urgency of integrating tawhidic principles into contemporary Islamic education to overcome fragmentation and restore its relevance to the holistic development of the Muslim community.